Fermentation of glucose by Zymomonas mobilis CP4 utilising continuous transient technique - João Batista Buzato (Semina: Ciências Exatas e Tecnológicas, 2003)
Ethanol production by Zymomonas mobilis CP4 under continuous transient operation has been investigated. The bacteria was grown under alternating glucose amplitudes of 2% and 5% (w/p) and cycle time values of 2, 4 and 6 hours. The ethanol production was compared to data obtained in simple chemostat operation grown 3.5%(w/v) glucose medium. The value of dilution rate was fixed as 0.2h-1 for both techniques. When cycle time value of 2 hours was used, values of biomass and ethanol kept constant. The appliance of cycle time of 4 hours produced smooth responses from the organisms. The values of biomass oscillated from 0.7 to 0.93 g/l. When cycle time of 6 hours was used the oscillations on biomass and ethanol were pronounced. The minimum and maximum values of biomass were respectively 0.61 and 1g/l. As far as conversion efficiency to ethanol is concerned the values of 84, 85 and 89% (corresponding to cycle time of 2, 4 and 6 hours) were found whereas conversion efficiency was low as 50% when simple chemostat was used.